The Relationship between Social Infrastructure and Happiness - Kim, Meeyoung; Im, Ha Na (Journal of Korea Planning Association, 2020)
As a social animal, human beings feel happy (or unhappy) in their relationships with others. This study tries to demonstrate the relationship between ‘social infrastructure’, the place that mediates social relations, and happiness. It is very important to study this relationship because the social infrastructure organizes and shapes everyday life in the city, and may contribute to enhancing the emotional well-being of urban dwellers. Using the ‘Civic Happiness Index Satisfaction Survey’ by Busan and ‘Neighborhood Unit Basic Living Infrastructure’ by the Ministry of Land, Infrastructure, and Transport (MOLIT) as data, the empirical results are as follows. First, social relations are highly related to happiness. Every indicator that represents social relations, such as ‘Personal-relationship Satisfaction’, ‘Job, Community or School Satisfaction’, ‘Social Participation Status’, ‘Experience on Discrimination’, ‘Respect on Human Rights’, and ‘Capability on Mobile Devices’ are significantly related to happiness. Second, social infrastructure, where social relations are practiced, is also relevant to happiness. Among 12 Neighborhood Unit Basic Living Infrastructures, four facilities (Kindergarten, Elementary School, Nursery, and Pharmacy) showed a significant relationship between their average distance from the residence and happiness. Although place is one of the crucial factors that affect human happiness, many studies on happiness nonetheless have overlooked the factor. This study is significant in that it verifies that place may either promote or undermine individual happiness, and thus spatial planning may contribute to happiness discourse. KCI Citation Count: 2